Legal Education Perspectives on Social Reactions and Sentencing Disparities in Mutilation Cases - Syalwah Az Zahra; Nailah Ikmal (Journal of Smart Pedagogy and Education, 2025)
This research examines the critical intersection of judicial decision-making, social media influence, and legal education regarding premeditated mutilation cases in Indonesia. Utilizing a hybrid normative-legal and socio-legal methodology, the study analyzes sentencing disparities under Article 340 of the Criminal Code and Law Number 1 of 2023. Findings reveal that systemic inconsistencies arise from a widespread failure to evaluate perpetrator motives and an increasing susceptibility to "penal populism" driven by the "no viral, no justice" phenomenon. Furthermore, the prevailing formalistic model of Indonesian legal education fails to equip jurists with necessary ethical and sociological reasoning to withstand digital public pressure. Consequently, this study advocates for a transformative shift toward Clinical Legal Education (CLE) and the implementation of standardized sentencing guidelines. Such reforms are essential to restore judicial integrity, fulfill the 2035 Judicial Road Map, and ensure that substantive justice prevails over procedural formalism within the evolving Indonesian criminal justice legal system.